The analysis of prognostic factors in patients with bone metastases from lung cancer - Brzozowska, Anna; Grzybowska, Ludmiła; Mazurkiewicz, Maria; Mazurkiewicz, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2001)
The aim of our study was to establish a correlation between chosen prognostic factors and survival time of patients with non small cell lung cancer (NSCLC) and bone metastases. A group of 82 patients with NSCLC after the radiotherapy of bone metastases was analized. Median survival time, counted from the end of radiotherapy of bone metastases to the decease was 3,7 months. Statistically significant correlation between the time of survival and 3 prognostic factors (such as previous treatment of lung cancer, biphosfonates treatment and systemic disease) was confirmed. There was no statistically significant dependence between age, gender, multiplicity of bone metastases and pathological fracture.